Crowdsourced social work educator technology standards - Counselman-Carpenter, Elisabeth (Teaching social work with digital technology, 2019)
This book was written to help social work educators make pedagogically sound, rational, practical, and ethical decisions about integrating technology into their social work programs and across the curriculum. It covers a range of essential topics, from understanding digital literacy skills to ethical implications for technology in social work practice, from using technology in the traditional classroom to fully online teaching environments. Case studies, practical examples, and technology tips are integrated into each chapter, and checklists show how technology is integrated with the Council on Social Work Education s EPAS competencies, the NASW s Code of Ethics, and other social work practice standards and guidelines. Appendices provide a wealth of practical materials.
Keywords: dept.swk

Applying accessibility practices across a curriculum - Marquart, M; Counselman-Carpenter, E (Teaching social work with digital technology, 2019)
This book was written to help social work educators make pedagogically sound, rational, practical, and ethical decisions about integrating technology into their social work programs and across the curriculum. It covers a range of essential topics, from understanding digital literacy skills to ethical implications for technology in social work practice, from using technology in the traditional classroom to fully online teaching environments. Case studies, practical examples, and technology tips are integrated into each chapter, and checklists show how technology is integrated with the Council on Social Work Education s EPAS competencies, the NASW s Code of Ethics, and other social work practice standards and guidelines. Appendices provide a wealth of practical materials.
Keywords: dept.swk

Case study – teaching online with students who are deaf - Marquart, M; Counselman-Carpenter, Elisabeth (Teaching social work with digital technology, 2019)
This book was written to help social work educators make pedagogically sound, rational, practical, and ethical decisions about integrating technology into their social work programs and across the curriculum. It covers a range of essential topics, from understanding digital literacy skills to ethical implications for technology in social work practice, from using technology in the traditional classroom to fully online teaching environments. Case studies, practical examples, and technology tips are integrated into each chapter, and checklists show how technology is integrated with the Council on Social Work Education s EPAS competencies, the NASW s Code of Ethics, and other social work practice standards and guidelines. Appendices provide a wealth of practical materials.
Keywords: dept.swk